2023
DOI: 10.1039/d2ob01886a
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated solid-phase synthesis of glycopeptides containing multipleN-glycosylated sites

Abstract: Peptide fragments of glycoproteins containing multiple N-glycosylated sites are essential biochemical tools not only to investigate protein-protein interactions but also to develop glycopeptide-based diagnostics and immunotherapy. However, solid-phase synthesis of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We applied Fmoc/ t Bu/OAc solid‐phase peptide synthesis (SPPS) for the efficient preparation of the MUC1 tandem repeat aglycone 1 and of the three differently glycosylated variants 2 , 3 , and 4 , carrying one, two, and three GalNAc monosaccharides, respectively, at specific Thr and/or Ser residues in the sequence (Scheme 1 and Figures S1–S4 in the Supporting Information). Fmoc−Thr[GalNAc(OAc) 3 ]−OH and Fmoc−Ser[GalNAc(OAc) 3 ]−OH were used as building blocks in SPPS to introduce O ‐glycosylation directly with complete control over position [29] …”
Section: Resultsmentioning
confidence: 99%
“…We applied Fmoc/ t Bu/OAc solid‐phase peptide synthesis (SPPS) for the efficient preparation of the MUC1 tandem repeat aglycone 1 and of the three differently glycosylated variants 2 , 3 , and 4 , carrying one, two, and three GalNAc monosaccharides, respectively, at specific Thr and/or Ser residues in the sequence (Scheme 1 and Figures S1–S4 in the Supporting Information). Fmoc−Thr[GalNAc(OAc) 3 ]−OH and Fmoc−Ser[GalNAc(OAc) 3 ]−OH were used as building blocks in SPPS to introduce O ‐glycosylation directly with complete control over position [29] …”
Section: Resultsmentioning
confidence: 99%
“…More recently, Bakhatan et al , 57 Naoum et al , 25,58 Alshanski et al , 26 and Strauss et al 27 reported higher yields in the SPS of peptides, glycopeptides, and glycans using mechanical stirring rather than gas bubbling; this improvement is attributed to the fact that mechanical stirring “increases the diffusion of both reagents and beads in a narrow dimension reactor”. 25 No distinction between external and internal diffusion was made.…”
Section: Momentum Transfer: Mixing In Spsmentioning
confidence: 99%
“…20,21 The need for further optimization regarding process time, cost, and yield, especially in AGA, has prompted renewed attention to the physical aspects of SPS, such as mixing and swelling. [22][23][24][25][26][27] Glycans are branched structures where regioand stereocontrol must be controlled throughout the synthesis. Consequently, carbohydrate building blocks are more complex and expensive than the precursors of linear molecules such as oligonucleotides and peptides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation